2020
DOI: 10.3390/microorganisms8111748
|View full text |Cite
|
Sign up to set email alerts
|

Diversify and Conquer: The Vaccine Escapism of Plasmodium falciparum

Abstract: Over the last century, a great deal of effort and resources have been poured into the development of vaccines to protect against malaria, particularly targeting the most widely spread and deadly species of the human-infecting parasites: Plasmodium falciparum. Many of the known proteins the parasite uses to invade human cells have been tested as vaccine candidates. However, precisely because of the importance and immune visibility of these proteins, they tend to be very diverse, and in many cases redundant, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 137 publications
0
7
0
Order By: Relevance
“…In fact, drug options are scarce and highly challenged by the emergence of resistant strains (Madhav and Hoda 2021). The same is observed for insecticides used to eliminate the vector Anopheles (Minetti et al 2020), and the available vaccines showed a low efficacy as stated in recently reviewed literature (Pance 2020).…”
Section: P-glycoprotein Modulation Activitymentioning
confidence: 87%
“…In fact, drug options are scarce and highly challenged by the emergence of resistant strains (Madhav and Hoda 2021). The same is observed for insecticides used to eliminate the vector Anopheles (Minetti et al 2020), and the available vaccines showed a low efficacy as stated in recently reviewed literature (Pance 2020).…”
Section: P-glycoprotein Modulation Activitymentioning
confidence: 87%
“…Human malaria is caused by 5 species of Plasmodium parasites of which P. falciparum is the most common and deadly while P. vivax and P. ovale form hypnozoites or dormant hepatic forms that cause recurrences of the disease and are difficult to clear. Though a vaccine (RTS,s/AS01) has recently been licensed to be deployed among African children [22], it has shown an efficacy of 30-50% so far, which is attributed to the immense genetic variability of worldwide populations of parasites [23]. The drugs currently used are losing efficacy due to increasing resistance of par- The ethical issues of embryonic stem cells have been avoided with the reprogramming of terminally differentiated cells back into pluripotency to generate iPS cells [13].…”
Section: Malariamentioning
confidence: 99%
“…Furthermore, there is a need to develop vaccines against the separate parasites with P. falciparum responsible for the majority of infections in Sub Sahara and P. vivax in South East Asia. The complexity of the genetic makeup of the parasites is also contributing to the delay in vaccination production, with the P. falciparum genome made of 5300 genes alone with demonstrable geographic diversity ( 28 ).…”
Section: Introductionmentioning
confidence: 99%